Women's experience of abortion : a qualitative study - Taylor, Gaye Lesley (Rhodes University, Faculty of Humanities, Department of Social Work, 1998)
Abortion is an emotive topic that always raises strong feelings. The purpose of this study, however, is not to focus on the religious, political or moral questions surrounding abortion. Abortion is a reality and in South Africa, where it has only recently become legal, there is a need to have an understanding of the effects on women in order to provide counselling services. There is also a need to provide services for the many women who have had illegal terminations in the past. This study reviewed the most recent literature on the subject and the researcher takes the view that although the scientific literature states there is little long term psychological effect of abortion, the non-positivist literature which records women's experiences tells another story. Some of the problems with the scientific literature is that psychological effects are not defined and there may be political motivation for the study, ie. an attempt is made to prove that the health costs are not high for abortion because there is little long term effect. The researcher, however, feels this does a disservice to women who have had abortions because there is a failure to provide counselling services. Some members of the feminist movement also deserve criticism because in their haste to give women their rights they fail to allow a woman to thoroughly explore her options beforehand and to provide support services afterwards. The researcher, however, also identified a new theme in the literature which has been called a maturing of the feminist viewpoint that along with the right to abortion, women also have a right to the mixed feelings that go with making, what is for many, a very painful decision. There is a recognition that abortion is about loss and thus there is a corresponding need to acknowledge women's need to mourn and to provide services. The study does not include the experience of women who seek abortions for reasons of poverty. It also excludes the experience of women who have abortions as a result of rape, incest or harm to the foetus. It is a qualitative study and a non-probability sampling technique which comprised snowball and purposive methods was used to identify respondents. In-depth semi-structured interviews using a broad theme of questions were conducted with five respondents. The women were asked to tell the stories of their abortions: their and their partner's feelings before and after, how they decided and the actual experience. They were also asked to identify counselling requirements, what they found helpful and what would have helped. The literature and the findings support the researcher's view that women who find themselves with an unexpected pregnancy need an opportunity to objectively consider all their options, namely keeping the baby, adoption or abortion, and to have an objective counsellor assist them in vigorously considering these. If they decide on a termination they need to be given as much information as possible about the procedure and about how they are likely to feel. Afterwards counselling should be made available and women should be encouraged to use the service. They need to be assisted to explore all ways of coming to terms with it such as through dream work, dialogueing with the unborn child through a letter and for those with religious beliefs seeking absolution from the church. There is a great need for a Christian and other religious ministry in this regard. Self-help therapies such as support groups can also be helpful
Keywords: Abortion; Abortion -- South Africa; Women -- Counseling of